The Ethics of Deep Brain Stimulation for the Treatment of Anorexia Nervosa - Maslen, Hannah (Neuroethics, 2015)
There is preliminary evidence, from case reports and investigational studies, to suggest that Deep Brain Stimulation (DBS) could be used to treat some patients with Anorexia Nervosa (AN). Although this research is at an early stage, the invasive nature of the intervention and the vulnerability of the potential patients are such that anticipatory ethical analysis is warranted. In this paper, we first show how different treatment mechanisms raise different philosophical and ethical questions. We distinguish three potential mechanisms alluded to in the neuroscientific literature, relating to desire, control, and emotion, respectively. We explain why the precise nature of the mechanism has important implications for the patient’s autonomy and personal identity. In the second part of the paper, we consider practical dimensions of offering DBS to patients with AN in certain cases. We first discuss some limited circumstances where the mere offering of the intervention might be perceived as exerting a degree of coercive pressure that could serve to undermine the validity of the patient’s consent. Finally, we consider the implications of potential effects of DBS for the authenticity of the patient’s choice to continue using stimulation to ameliorate their condition.